Juxtaglomerular cell tumor as a rare cause of hypertension in adults - Chambô, José L.; Falci Jr., Renato; Lucon, Antonio M. (FapUNIFESP (SciELO), 2004)
The juxtaglomerular cell tumor is a cause of secondary hypertension in adults. A 35-year-old female patient suffering from hypertension and low serum potassium had a 3 × 3 cm solid mass at the lower pole of left kidney diagnosed by abdominal sonography. Partial nephrectomy was performed and the postoperatory was uneventful. Normalization of blood pressure was observed within the first month.
Keywords: Juxtaglomerular apparatus; Kidney neoplasms; Urologic neoplasms; enalapril; potassium; adult; case report; computer assisted tomography; Doppler echography; female; histopathology; human; human tissue; hypertension; hypokalemia; immunohistochemistry; juxtaglomerular cell; kidney mass; kidney tumor; partial nephrectomy; physical examination; potassium blood level; treatment outcome; tumor volume; Adult; Female; Humans; Hypertension, Renal; Juxtaglomerular Apparatus; Kidney Neoplasms